Northern Rover: The Life Story of Olaf Hanson - A.L. Karras (Athabasca University Press, 2008)
From 1919 to 1970, Olaf Hanson was a trapper, fur trader, prospector, game guardian, fisherman, and road blasting expert in northeastern Saskatchewan. He told his life story to popular Saskatchewan author A. L. Karras, who wrote this historical memoir in the 1980s. In an uncompromising, straightforward style, Karras and Hanson reveal the geography, wildlife, natural history of the region as well as the business and social interactions between people. Their book offers a look at the vanished subsistence and commercial economy of the boreal forest, wound around a fascinating personal story of courage and physical stamina.